The Effect Of Co-Production On Sustainable Business Performance: Moderating Effect Of Internet Of Things - Lee, Eu Chun (2013)
The objective of this study is to develop a co-production concept in achieving long term sustainable business performance and innovation performance for an electrical and electronic organization. This study proposed to contribute the knowledge of coproduction and give a new idea for electrical and electronic manufacturing practice. The study has covered the electrical and electronic operation and production sectors that been found in the Malaysia region. Malaysia is suitable for me to conduct this study is basically due to it has the highest GDP in electrical and electronic manufacturing facilities